Holocene circum-Mediterranean vegetation changes: Climate forcing and human impact - Jalut, Guy; Dedoubat, Jean Jacques; Fontugne, Michel; Otto, Thierry (Quaternary International, 2009)
The Mediterranean climate and its variability depend on global-scale climate patterns. Close correlations appear when comparing Holocene palaeoenvironmental data (lake levels, ﬂuvial activity, Mediterranean surface temperature and salinity, marine sedimentation) with the main stages of the history of the circum-Mediterranean vegetation. They indicate an evolution of the Mediterranean biome controlled by the climate and emphasize the teleconnections between the climate of the Mediterranean area and the global climatic system. In the circum-Mediterranean area, the Holocene can be divided into three periods: a lower humid Holocene (11 500–7000 cal BP) interrupted by dry episodes; a transition phase (7000–5500 cal BP) during which occurred a decrease in insolation as well as the installation of the present atmosphere circulation in the northern hemisphere; and an upper Holocene (5500 cal BP—present) characterized by an aridiﬁcation process. Throughout the Holocene, humans used and modiﬁed more or less strongly the environment but the climatic changes were the determining factors of the evolution of the Mediterranean biome. Societies had to adapt to natural environmental variations, their impact on the environment increasing the ecological consequences of the global changes.
Keywords: climate; climatic changes; Holocene; Mediterranean area; pollen data; vegetation dynamics (voyant)

Holocene circum-Mediterranean vegetation changes: Climate forcing and human impact - Jalut, Guy; Dedoubat, Jean Jacques; Fontugne, Michel; Otto, Thierry (Quaternary International, 2009)
The Mediterranean climate and its variability depend on global-scale climate patterns. Close correlations appear when comparing Holocene palaeoenvironmental data (lake levels, ﬂuvial activity, Mediterranean surface temperature and salinity, marine sedimentation) with the main stages of the history of the circum-Mediterranean vegetation. They indicate an evolution of the Mediterranean biome controlled by the climate and emphasize the teleconnections between the climate of the Mediterranean area and the global climatic system. In the circum-Mediterranean area, the Holocene can be divided into three periods: a lower humid Holocene (11 500–7000 cal BP) interrupted by dry episodes; a transition phase (7000–5500 cal BP) during which occurred a decrease in insolation as well as the installation of the present atmosphere circulation in the northern hemisphere; and an upper Holocene (5500 cal BP—present) characterized by an aridiﬁcation process. Throughout the Holocene, humans used and modiﬁed more or less strongly the environment but the climatic changes were the determining factors of the evolution of the Mediterranean biome. Societies had to adapt to natural environmental variations, their impact on the environment increasing the ecological consequences of the global changes.
Keywords: climate; climatic changes; Holocene; Mediterranean area; pollen data; vegetation dynamics (voyant)

Soil evolution over the Quaternary period in a Mediterranean climate (SE Spain) - Ortiz, I; Simón, M; Dorronsoro, C; MartÄ±n, F; GarcÄ±a, I (Catena, 2002)
Palaeosols in the Granada Basin (SE Spain) have been studied in two different situations: surface soils on geomorphically stable surfaces since the Early Pleistocene with younger pedogenic overprinting and buried soils on unstable surfaces from the Middle –Late Pleistocene on which successive erosional – depositional episodes have alternated with pedogenic episodes. For each soil clay and iron accumulation indices, the Fet + Al t /Si t ratio, clay mineralogy and micromorphological features were used to estimate the degree of soil development. From the Early to the early Late Pleistocene, the main pedogenic processes were the leaching of carbonates, weathering, illuviation and rubification, which resulted in Bt horizons with red colours, clay texture, clay coatings and kaolinite neoformation. The degree of weathering and the development of these Bt horizons varied over time, and the soils that formed on the surfaces from the Early Pleistocene show strongest weathering and development. However, after their formation, there were periods in which they were partially truncated and recalcified, resulting in polygenetic soils. The different degrees of development of the buried soils during the last 474,000 years indicate that the wettest warm period was stage 7 and the driest, stage 5. Stages 9 and 11 must have had climates with intermediate wetness. Since the clay accumulation and iron oxide accumulation indices, the differences in Fet + Al t /Si t ratio between Bt and C horizons, the extent of kaolinite neoformation and the micromorphological features of the soils formed during stage 7 are all similar to the surface soils that formed on Early Pleistocene deposits, these features cannot be used to date surfaces older than 242,000 BP. By contrast, the soils that formed during stage 7 and later periods show different extents of development and thus can be used for the approximate dating of landforms.
Keywords: Buried soils; climatic changes; Pleistocene; Relict soils; Soil development

Soil evolution over the Quaternary period in a Mediterranean climate (SE Spain) - Ortiz, I.; Simón, M.; Dorronsoro, C.; MartÄ±n, F.; GarcÄ±a, I. (Catena, 2002)
Palaeosols in the Granada Basin (SE Spain) have been studied in two different situations: surface soils on geomorphically stable surfaces since the Early Pleistocene with younger pedogenic overprinting and buried soils on unstable surfaces from the Middle –Late Pleistocene on which successive erosional – depositional episodes have alternated with pedogenic episodes. For each soil clay and iron accumulation indices, the Fet + Al t /Si t ratio, clay mineralogy and micromorphological features were used to estimate the degree of soil development. From the Early to the early Late Pleistocene, the main pedogenic processes were the leaching of carbonates, weathering, illuviation and rubification, which resulted in Bt horizons with red colours, clay texture, clay coatings and kaolinite neoformation. The degree of weathering and the development of these Bt horizons varied over time, and the soils that formed on the surfaces from the Early Pleistocene show strongest weathering and development. However, after their formation, there were periods in which they were partially truncated and recalcified, resulting in polygenetic soils. The different degrees of development of the buried soils during the last 474,000 years indicate that the wettest warm period was stage 7 and the driest, stage 5. Stages 9 and 11 must have had climates with intermediate wetness. Since the clay accumulation and iron oxide accumulation indices, the differences in Fet + Al t /Si t ratio between Bt and C horizons, the extent of kaolinite neoformation and the micromorphological features of the soils formed during stage 7 are all similar to the surface soils that formed on Early Pleistocene deposits, these features cannot be used to date surfaces older than 242,000 BP. By contrast, the soils that formed during stage 7 and later periods show different extents of development and thus can be used for the approximate dating of landforms.
Keywords: Buried soils; climatic changes; Pleistocene; Relict soils; Soil development

Holocene climatic changes in the Western Mediterranean, from south-east France to south-east Spain - Jalut, Guy; Esteban Amat, Augustin; Bonnet, Louis; Gauquelin, Thierry; Fontugne, Michel (Palaeogeography, Palaeoclimatology, Palaeoecology, 2000)
Holocene climatic changes along coastal regions from south-east France to south-east Spain were studied using pollen ratios. Comparing modern pollen rain, vegetation and climate along selected transects from the Atlantic Ocean to the Mediterranean, we obtained threshold values of two diVerent ratios corresponding to the diVerent climatic conditions along the transects. These pollen ratios and threshold values were employed to characterize the Holocene climatic changes from nine Mediterranean coastal sites. The results were compared with data from marine and continental pollen sequences distributed in the western Mediterranean basin, and with additional regional data independent of human activity: lake-level ﬂuctuations, alpine glacier advance and retreat chronology, 14C anomaly and cooling phases in Eastern France and Central Europe. The role of anthropogenic activities and climate on the changes in vegetation is discussed. Six major changes in vegetation cover were identiﬁed. They correspond to aridiﬁcation phases that occurred around 9500–9000 yr BP (10 900–9700 cal BP), 7500–7000 yr BP (8400–7600 cal BP), 4500–4000 yr BP (5300–4200 cal BP), 3700–3300 yr BP (4300–3400 cal BP), 2600–1900 yr BP (2850–1730 cal BP) and 1300–1000 yr BP (1300–750 cal BP). These arid episodes were regional responses to more global climatic changes and determined the changes in the vegetation cover. Humans undoubtedly enhanced the vegetation changes, but none the less had to adapt to these new climatic conditions.
Keywords: climatic changes; holocene vegetation; human impact; pollen data; western Mediterranean